Mammea B/BA Isolated From the Seeds of Mammea americana L. (Calophyllaceae) is a Potent Inhibitor of Methicillin-Resistant Staphylococcus aureus - Pájaro-González, Yina; Oliveros-Díaz, Andrés F.; Cabrera-Barraza, Julián; Fernández-Daza, Eduardo; Reyes, Niradiz; Montes-Guevara, Oscar A.; Caro-Fuentes, Daneiva; Franco-Ospina, Luis; Quiñones- Fletcher, Wiston; Quave, Cassandra L.; Díaz-Castillo, Fredyc (Frontiers in Pharmacology, 2022)
Staphylococcus aureus remains a pathogen of high concern in public health programs worldwide due to antibiotic resistance and emergence of highly virulent strains. Many phytochemicals have demonstrated activity against S. aureus and other gram-positive bacteria, but MIC values comparable to commonly used antibiotics are needed. In the present study, the ethanol extract of seeds of Mammea americana and its fractions were tested against S. aureus strains that are sensitive and resistant to methicillin; six mammea coumarins were obtained from the active fraction. The extract inhibited the growth of S. aureus with MIC values of 2-4 µg/mL and was bactericidal at a concentration of 8 µg/mL in all strains evaluated. Mammea B/BA (MaBBA) presented MIC values in a range between 0.5 to 1.0 µg/mL in six methicillin-sensitive strains and eight methicillin-resistant strains evaluated. We consider MaBBA the most potent of all mammea coumarins reported to date, according to the literature review carried out at the time of writing of this article. Toxicity assessment of the extract and the compound MaBBA against the nematode C. elegans and human fibroblasts, indicated that both had low toxicity in the in vivo and in vitro tests carried out